2020
DOI: 10.1007/s00382-020-05256-9
|View full text |Cite
|
Sign up to set email alerts
|

On the impact of atmospheric vs oceanic resolutions on the representation of the sea surface temperature in the South Eastern Tropical Atlantic

Abstract: Despite the efforts of the modelling community to improve the representation of the sea surface temperature (SST) over the South Eastern Tropical Atlantic, warm biases still persist. In this work we use four different configurations of the fullycoupled AWI Climate Model (AWI-CM) which allow us to gain physics-based insight into the role of the oceanic and atmospheric resolutions of the model in the regional distribution of the SST. Our results show that a sole refinement of the oceanic resolution reduces warm … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 16 publications
(17 citation statements)
references
References 65 publications
0
16
0
Order By: Relevance
“…There is a greater understanding of the causes of tropical Atlantic biases: The equatorial Atlantic SST biases are linked to too weak trade winds in boreal spring (Richter and Xie 2008;Wahl et al 2011;Voldoire et al 2019); whereas southeastern tropical Atlantic bias has been related to the misrepresentation of (1) the persistent low level cloud cover (Zuidema et al 2016), (2) along shore coastal winds (Xu et al 2014a;Koseki et al 2018) and (3) coastal upwelling (Xu et al 2014b). Several studies have shown that increasing atmospheric model resolution can reduce tropical Atlantic biases, especially in the southeastern Atlantic (Small et al 2015;Milinski et al 2016;Harlaß et al 2018), whereas de la Vara et al (2020) have shown improvements from increasing oceanic model resolution. While detecting the cause of the bias and formulating a solution that is computationally tractable is most desirable, the remaining bias even in the computationally demanding systems (e.g., Harlaß et al 2018) is still large (about 2-3 • C ).…”
Section: Supplementary Informationmentioning
confidence: 99%
“…There is a greater understanding of the causes of tropical Atlantic biases: The equatorial Atlantic SST biases are linked to too weak trade winds in boreal spring (Richter and Xie 2008;Wahl et al 2011;Voldoire et al 2019); whereas southeastern tropical Atlantic bias has been related to the misrepresentation of (1) the persistent low level cloud cover (Zuidema et al 2016), (2) along shore coastal winds (Xu et al 2014a;Koseki et al 2018) and (3) coastal upwelling (Xu et al 2014b). Several studies have shown that increasing atmospheric model resolution can reduce tropical Atlantic biases, especially in the southeastern Atlantic (Small et al 2015;Milinski et al 2016;Harlaß et al 2018), whereas de la Vara et al (2020) have shown improvements from increasing oceanic model resolution. While detecting the cause of the bias and formulating a solution that is computationally tractable is most desirable, the remaining bias even in the computationally demanding systems (e.g., Harlaß et al 2018) is still large (about 2-3 • C ).…”
Section: Supplementary Informationmentioning
confidence: 99%
“…This has been generally attributed to a spurious weakening of the northward Benguela Current, as well as to an underestimation of the strength of the Benguela low-level jet [87,88]. It has also been proposed that, even when the simulated upwelling intensity is well captured, the misrepresentation of the sharp thermocline characteristic of the TA culminates in upwelling of waters which are warmer than observed, therefore contributing to coastal SST biases [34,129]. In turn, the simulated southward Angola Current tends to be stronger than in observations due to an excessive negative wind stress curl in the near shore [91,130].…”
Section: Modeling the Climate Of The Tamentioning
confidence: 99%
“…Also, an incorrect simulation of global circulation can affect the simulation of the SETA climate, as a weak Atlantic meridional overturning circulation (AMOC; [144]) seems to be associated to a warm SETA bias. Also, failures in the representation of the South Atlantic Anticyclone south of 20 • S [34] and an incorrect representation of the Agulhas leakage [129] could be important contributors to the warm bias in the tropical Atlantic. Also, the authors of [145] found that cloud biases in the Southern Ocean could be accountable for a large part of the double ITCZ bias.…”
Section: Modeling the Climate Of The Tamentioning
confidence: 99%
“…12f). Also, the along-shore wind in ROM decreases rapidly towards the coast, giving a strong wind-stress curl, which causes enhanced upwelling over a narrow coastal strip (e.g., de la Vara et al 2020). In addition, the active air-sea coupling leads to a better heat exchange and thus to a larger influence of the ocean surface temperature onto the air temperature.…”
Section: What Causes the Temperature Changes Observed In The Iberian Peninsula?mentioning
confidence: 99%
“…As discussed in former works, we need an oceanic eddy-permitting resolution to simulate the most relevant features of the North Atlantic circulation (Marzocchi et al 2015) and enhanced atmospheric resolution to represent adequately the storm-track response to global warming (Willison et al 2015) and extratropical cyclone activity, especially to the northeast of the North Atlantic (Michaelis et al 2017). It was also suggested that changes in the land-sea temperature gradient will induce changes in the along-shore winds in the eastern boundary upwelling systems which could depend on model resolution (de la Vara et al 2020). In the Mediterranean, it was found that coupling improves the simulated wind speed (particularly near coastal areas) and subsequently the turbulent heat fluxes (Akhtar et al 2018).…”
Section: Introductionmentioning
confidence: 99%